U.S. POLICY IN TAJIKISTAN: FROM RECOGNITION OF ITS INDEPENDENCE TO PARTNERSHIP - ABDULLO, Rashid (CENTRAL ASIA AND THE CAUCASUS, 2007)
Tajikistan’s relations with the United States are just as important for it as those with Russia and China. While relations with Russia have two equally important components (economic and political, the military dimension included) and its relations with China are economy-dominated, Tajikistan’s contacts with America cannot be described in figures, at least to a much lesser extent than the relations with the two other members of the Big Three. Today, the political element, with military technical cooperation as its component, is the only significant aspect of Tajik American relations. This absolute domination of the political element in bilateral relations is unlikely to be changed, at least in the near future. From the very first days of its independence, Tajikistan has regarded its stable relations with the United States as a strategic task, a guarantee of its newly acquired sovereignty, which, in its turn, guaranteed the Tajiks’ ethnic security and a stronger Tajik statehood. Security was, and still is, interpreted as the sum total of the political, economic, and other conditions under which the Tajiks will survive as an ethnos with an ethnic identity of its own. The Tajik leaders were absolutely convinced that as soon as the Soviet republic adopted its declaration of independence, the United States would hasten to recognize Tajikistan’s new status as an independent state. They argued that this would have been a logical political move for a country that had been the Soviet Union’s political and ideological foe for many years and that had been working toward the U.S.S.R.’s disintegration. The West and the United States, however, did not hasten to take this step. This did not happen until the Soviet Union fell apart de jure. After recognizing Tajikistan’s independence, the United States found itself facing another difficult choice. While the other Central Asian republics reached independence as fairly united countries with commonly recognized national leaders, Tajikistan entered the new historical epoch amid a ruthless power struggle that flared up back in February 1990 while the federal state was dying. Each of the conflicting sides counted on the Americans. U.S. Secretary of State James Baker, who visited Dushanbe in February 1992, created a new impetus for the relations between the two countries, and not only because it was the first visit of a high-ranking American bureaucrat to the newly independent state